Effects of long-term tenofovir-based combination antiretroviral therapy in HIV-hepatitis B virus coinfection on persistent hepatitis B virus viremia and the role of hepatitis B virus quasispecies diversity. (19th June 2016) - Audsley, Jennifer; Bent, Stephen J.; Littlejohn, Margaret; Avihingsanon, Anchalee; Matthews, Gail; Bowden, Scott; Bayliss, Julianne; Luciani, Fabio; Yuen, Lilly; Fairley, Christopher K.; Locarnini, Stephen; Lewin, Sharon R.; et al.
Abstract : Objective: Hepatitis B virus (HBV) can persist in some HIV–HBV coinfected individuals on tenofovir disoproxil fumarate (TDF)-containing combination antiretroviral therapy (cART) but HBV resistance to TDF has not been reported and the source of persistent HBV DNA on TDF is poorly understood. The aims of this study were to assess long-term HBV suppression in HIV–HBV coinfected individuals receiving TDF and investigate quasispecies variation using ultradeep pyrosequencing (UDPS). Methods: Ninety-two HIV–HBV coinfected participants on, or about to commence, TDF-containing cART were enrolled [Australia ( n  = 40), Thailand ( n  = 52)] and followed for 2 years with study visits every 6 months. HBV reverse transcriptase sequencing was performed on samples with HBV DNA more than 400 IU/ml by population-based methods and UDPS. Quasispecies diversity was assessed using Shannon entropy. Results: Over 24 months, viremia was detected at least once in 17% ( n  = 16) of the cohort. Novel mutations were not identified in on TDF samples tested by population-based sequencing ( n  = 19). Using UDPS, the median Shannon entropy value in samples prior to TDF in patients aviremic on TDF was not statistically different from those who were viremic on TDF ( n  = 50; 8.4 and 9.1, respectively, P  = 0.9). Longitudinal Shannon entropy analysis of on TDF samples from five participants showed three individuals with significant changes in viral diversity over time. Conclusion: Persistent viremia on TDF-containing cART is common but TDF-resistance was not detected. In some individuals, changes in viral diversity over time were observed on TDF which could potentially be active viral replication. Further follow-up will be needed to determine the clinical significance of detectable HBV DNA on TDF-containing cART.